The causal effect of Internet use on rural middle-aged and older adults’ depression: A propensity score matching analysis - Junqi Ma (Digital Health)
Objective Depression among older adults is increasingly becoming a global public health issue. Along with the rapid development of digital information technology, the Internet has profoundly changed the lifestyle of older adults. However, few studies have focused on the mental health of rural middle-aged and older adult populations, and this study aims to explore the impact of Internet use on depressive symptoms among rural middle-aged and older adults. Methods Our study is based on 10,946 Chinese rural participants aged 45 and above in the 2018 China Health and Retirement Longitudinal Study (CHARLS). Depression is measured by a 10-item Centre for Epidemiologic Studies (CES-D10), and multiple linear regression and the propensity score matching (PSM) method are used to examine the effect of Internet use on depression in Chinese rural middle-aged and older adults. Results Internet use significantly reduced depression in rural middle-aged and older adults. The mechanism was that Internet use improved mental health by improving social interaction and enhancing social support. Furthermore, desk computer, laptop computer, and cellphone use were all significantly associated with lower depression scores compared to non-Internet users. And the more the content of Internet use, the significantly lower the level of depression in rural middle-aged and older adults. Heterogeneity analysis showed that Internet use reduced depression more pronounced in the groups of males, those in elementary and secondary education, low-medium income, and aged under 75. Conclusion The paper confirms that Internet use significantly reduces depression, with social interaction and social support playing a mediating role. The results of the study show that strengthening rural Internet infrastructure can promote healthy aging in rural areas.